2020
DOI: 10.1177/0885066620957946
|View full text |Cite
|
Sign up to set email alerts
|

Medical Malpractice Claims Involving Physicians in the Intensive Care Unit: A Cohort Study

Abstract: Background: The intensive care unit (ICU) is a fast-paced setting, in which physicians from different specialties work. The goal of this study is to understand whether characteristics of medical malpractice claims occurring in the ICU differ by physician specialty. Methods: A retrospective cohort study was performed using a national database called the Comparative Benchmarking System, which is operated by Harvard’s malpractice insurer. Claims were included if the harm events occurred in the ICU and closed betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…These studies reached mixed conclusions on the impact of the number of codefendants on medical litigation. A few studies have concluded that the number of codefendants was not a significant predictor of defendants’ verdicts, 31 nor was it a significant predictor of the amount of compensation paid for patients in claims against medical intensive care unit physicians 45 . Conversely, analyzed medical malpractice cases in Texas found that more than 50% of cases with high paid compensations included 2 or more codefendants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies reached mixed conclusions on the impact of the number of codefendants on medical litigation. A few studies have concluded that the number of codefendants was not a significant predictor of defendants’ verdicts, 31 nor was it a significant predictor of the amount of compensation paid for patients in claims against medical intensive care unit physicians 45 . Conversely, analyzed medical malpractice cases in Texas found that more than 50% of cases with high paid compensations included 2 or more codefendants.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few previous studies have included the number of codefendants as part of analyzing medical litigation. 31,44,45 These studies reached mixed conclusions on the impact of the number of codefendants on medical litigation. A few studies have concluded that the number of codefendants was not a significant predictor of defendants' verdicts, 31 nor was it a significant predictor of the amount of compensation paid for patients in claims against medical intensive care unit physicians.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the first example, Ranum et al (2021) review anesthesia-related cases in ambulatory surgery settings. Myers (2021) focused her examination on cases against physicians in the intensive care unit. Finally, Prieto et al (2022) analyzed cases involving pediatric surgery cases.…”
Section: Focus On Specific Settingsmentioning
confidence: 99%
“…Another study that focused on a specific set of providers in a particular setting was conducted by Myers (2021), who evaluated cases against physicians in the intensive care unit (ICU) over a 10-year period. The CBS data included 1,113 cases involving injury claims specific to physicians in the ICU, which were further analyzed by comparing the specialty of each primary physician named in the case.…”
Section: Focus On Specific Settingsmentioning
confidence: 99%